Perancangan Aplikasi Media Pembelajaran Edukasi Anak Berbahasa Inggris Berbasis Android : (Studi Kasus Paud Nurul Iman) - Yuntari PURBASARI (JSK ( Jurnal Sistem Informasi dan Komputerisasi Akuntansi ), 2022)
Paud Nurul Iman is a place to conduct teaching and learning activities for early childhood in the Prabumulih area. Paud Nurul Iman still conducts teaching and learning activities manually where children still use blackboards, books and teaching aids in learning English. Based on the results of this study, the researchers tried to design an Android-based learning media application using the prototype method to make it easier for teachers and students to carry out the teaching and learning process. With this learning media application, it is hoped that it can help teachers in teaching English to students so that the teaching and learning process becomes more interesting.